The CHIME Fast Radio Burst Project: System Overview - Amiri, M.; Bandura, K.; Berger, P.; Bhardwaj, M.; Boyce, M. M.; Boyle, P. J.; Brar, C.; Burhanpurkar, M.; Chawla, P.; Chowdhury, J.; Cliche, J.-F.; Cranmer, M. D.; et al. (The Astrophysical journal, 2018)
The Canadian Hydrogen Intensity Mapping Experiment (CHIME) is a novel transit radio telescope operating across the 400-800 MHz band. CHIME is composed of four 20 m × 100 m semicylindrical paraboloid reflectors, each of which has 256 dual-polarization feeds suspended along its axis, giving it a 200 deg2 field of view. This, combined with wide bandwidth, high sensitivity, and a powerful correlator, makes CHIME an excellent instrument for the detection of fast radio bursts (FRBs). The CHIME Fast Radio Burst Project (CHIME/FRB) will search beam-formed, high time and frequency resolution data in real time for FRBs in the CHIME field of view. Here we describe the CHIME/FRB back end, including the real-time FRB search and detection software pipeline, as well as the planned offline analyses. We estimate a CHIME/FRB detection rate of 2-42 FRBs sky-1 day-1 normalizing to the rate estimated at 1.4 GHz by Vander Wiel et al. Likely science outcomes of CHIME/FRB are also discussed. CHIME/FRB is currently operational in a commissioning phase, with science operations expected to commence in the latter half of 2018.